Meningkatkan Hasil Belajar Ipa Dengan Menggunakan Metode Demonstrasi Pada Siswa Kelas IV SDN 1 Daleman - Rustanto, Aris (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Based on the results of observations carried out at SD Negeri 1 Daleman, it turns out that teachers tend to teach in an informative way or only transfer knowledge from teacher to student so that students are not actively involved in the learning process. Students also do not fully like the subject (science) which is caused by a lack of interest in learning. This has an impact on the low results of daily tests, most of which are still below the minimum completeness criteria (KKM) that have been set, namely 62, of the 17 students who have met the minimum completeness standards, there are only 2 children or only 11.7%. Meanwhile, 15 other children or 88.3% have not reached the specified KKM. Conclusion: The application of the demonstration method can improve student learning achievement in science subjects regarding forces (push and pull) that can change shape. This is shown by the increase in the average student learning outcomes and the percentage of learning completion in each cycle, namely in the pre-cycle from 3 students or 11.7% who completed, to 9 students or 52.9% in cycle 1 and increasing to 14 students or 82.3% at the end of Cycle 2. While the average value was from 56.8 in the pre-cycle to 62.2 in Cycle 1 and increased to 68.7 at the end of Learning Cycle 2.